Fatigue Crack Growth Rate of an Al-Cu-Mg Alloy. Issue 3 (February 2019) - He, Jun; Liu, Yilun; Liu, Chi; Wang, Qing; Ma, Liyong
Abstract: In this study, fatigue crack growth rates of industrial 2524-T3 aluminium alloy plates under various stress ratios R ( R = 0.1, 0.2, 0.3, and 0.5) were examined. The microstructure was observed by using a scanning electron microscope (SEM). The results showed that, for a given stress intensity factor range Δ K, the increase in stress ratio led to an increase in fatigue crack growth rate. Besides, the SEM images showed that the fatigue striations were predominant in the fracture, and the spacing of the fatigue striations also drastically increased as the stress ratio increased in different samples. This phenomenon can be explained well by crack closure effects.